Henry Versus Thompson Approach for Fixation of Proximal Third Radial Shaft Fractures: A Multicenter Study. Issue 2 (February 2020) - Dashe, Jesse; Murray, Brett; Tornetta, Paul; Grott, Kelly M.; Mullis, Brian; Bellevue, Kate D.; Firoozabadi, Reza; Kempegowda, Harish; Horwitz, Daniel S.; Patel, Shaan; Fontenot, Philip B.; Mir, Hassan R.; et al.
Abstract : Objective: To compare the volar Henry and dorsal Thompson approaches with respect to outcomes and complications for proximal third radial shaft fractures. Design: Multicenter retrospective cohort study. Patients/Participants: Patients with proximal third radial shaft fractures ± associated ulna fractures (OTA/AO 2R1 ± 2U1) treated operatively at 11 trauma centers were included. Intervention: Patient demographics and injury, fracture, and surgical data were recorded. Final range of motion and complications of infection, neurologic injury, compartment syndrome, and malunion/nonunion were compared for volar versus dorsal approaches. Main Outcome: The main outcome was difference in complications between patients treated with volar versus dorsal approach. Results: At an average follow-up of 292 days, 202 patients (range, 18–84 years) with proximal third radial shaft fractures were followed through union or nonunion. One hundred fifty-five patients were fixed via volar and 47 via dorsal approach. Patients treated via dorsal approach had fractures that were on average 16 mm more proximal than those approached volarly, which did not translate to more screw fixation proximal to the fracture. Complications occurred in 11% of volar and 21% of dorsal approaches with no statistical difference. Conclusions: There was no statistical difference in complication rates between volar and dorsal approaches. Specifically, fixation to the level of the tuberosity is safely accomplished via the volar approach. This series demonstrates the safety of the volar Henry approach for proximal third radial shaft fractures. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.